Health screening results of Cubans settling in Texas, USA, 2010–2015: A cross-sectional analysis - Seagle, Emma E. (PLoS Med, 2020)
BACKGROUND: Protecting the health of refugees and other migrant populations in the United States is key to ensuring successful resettlement. Therefore, to identify and address health concerns early, the US Centers for Disease Control and Prevention (CDC) recommends a domestic medical examination (screening for infectious and noninfectious diseases/conditions) shortly after arrival in the US. However, because refugee/migrant populations often have differing health patterns from one another and the US population, the collection and analysis of health information is key to developing population-specific clinical guidelines to guide the care of resettled individuals. Yet little is known regarding the health status of Cubans resettling in the US. Among the tens of thousands of Cuban migrants who have resettled in the US, some applied as refugees in Cuba, some applied for parole (a term used to indicate temporary US admission status for urgent humanitarian reasons or reasons of public benefit under US immigration law) in Cuba, and others applied for parole status after crossing the border. These groups were eligible for US government benefits to help them resettle, including a domestic medical examination. We reviewed health differences found in these examinations of those who were determined to be refugees or parolees in Cuba and those who were given parole status after arrival. METHODS AND FINDINGS: We conducted a retrospective cross-sectional analysis of the Texas Department of State Health Services database. Cubans who arrived from 2010 to 2015 and received a domestic medical examination in Texas were included. Those granted refugee/parolee status in Cuba were listed in federal databases for US-bound refugees/parolees; those who were paroled after arrival were not listed. Overall, 2,189 (20%) obtained either refugee or parolee status in Cuba, and 8,709 (80%) received parolee status after arrival. Approximately 62% of those who received parolee status after arrival at the border were male, compared with 49% of those who obtained prior refugee/parolee status in Cuba. Approximately one-half (45%) of those paroled after arrival were 19–34 years old (versus 26% among those who obtained refugee/parolee status in Cuba). Separate models were created for each screening indicator as the outcome, with entry route as the main exposure variable. Crude and adjusted prevalence ratios were estimated using PROC GENMOD procedures in SAS 9.4. Individuals paroled after arrival were less likely to screen positive for parasitic infections (9.6% versus 12.2%; adjusted prevalence ratio: 0.79, 0.71–0.88) and elevated blood lead levels (children ≤16 years old, 5.2% versus 12.3%; adjusted prevalence ratio: 0.42, 0.28–0.63). Limitations include potential disease misclassification, missing clinical information, and cross-sectional nature. CONCLUSIONS: Within-country variations in health status are often not examined in refugee populations, yet they are critical to understand granular health trends. Results suggests that the health profiles of Cuban Americans in Texas differed by entry route. This information could assist in developing targeted screenings and health interventions.